An International Network of Magnetic Observatories. (15th October 2013) - Love, Jeffrey J.; Chulliat, Arnaud
Abstract : Since its formation in the late 1980s, the International Real‐Time Magnetic Observatory Network (INTERMAGNET), a voluntary consortium of geophysical institutes from around the world, has promoted the operation of magnetic observatories according to modern standards [e.g., Rasson, 2007]. INTERMAGNET institutes have cooperatively developed infrastructure for data exchange and management as well as methods for data processing and checking. INTERMAGNET institutes have also helped to expand global geomagnetic monitoring capacity, most notably by assisting magnetic observatory institutes in economically developing countries by working directly with local geophysicists.